2009
DOI: 10.1002/ejoc.200900431
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant neo‐Clerodane Diterpenoids from Scutellaria barbata

Abstract: Four new neo-clerodane diterpenoids, barbatines A-D (1-4), have been isolated from the whole plant of Scutellaria barbata (Lamiaceae), along with the known scutebarbatine A (5), and their structures determined by spectral analysis, including mass spectrometry and 2D NMR spectroscopy. The absolute configurations of 2 and 5 were established from their CD spectra by using the exciton chirality rule. A bioge-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…366 The absolute stereochemistry 1 R ,5 R ,6 R ,7 S ,8 R ,9 R ,10 R ,13 S was assigned to compounds 1045 ( 1048 ) and 1049 , whereas compound 1050 has the same 5 R ,6 R ,7 S ,8 R ,9 R ,10 R ,11 S ,13 R absolute configuration as 1051 . 379 Barbatine A ( 1050 ) also showed significant capability to protect cells against H 2 O 2 with an ED 50 value of 16.8 μM. 379 Barbatellarine C ( 1053 ) is a C-13 epimer of barbatellarine D ( 1054 ), as confirmed by a NOE difference experiment and the respective NOESY spectra.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 87%
See 1 more Smart Citation
“…366 The absolute stereochemistry 1 R ,5 R ,6 R ,7 S ,8 R ,9 R ,10 R ,13 S was assigned to compounds 1045 ( 1048 ) and 1049 , whereas compound 1050 has the same 5 R ,6 R ,7 S ,8 R ,9 R ,10 R ,11 S ,13 R absolute configuration as 1051 . 379 Barbatine A ( 1050 ) also showed significant capability to protect cells against H 2 O 2 with an ED 50 value of 16.8 μM. 379 Barbatellarine C ( 1053 ) is a C-13 epimer of barbatellarine D ( 1054 ), as confirmed by a NOE difference experiment and the respective NOESY spectra.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 87%
“…379 Barbatine A ( 1050 ) also showed significant capability to protect cells against H 2 O 2 with an ED 50 value of 16.8 μM. 379 Barbatellarine C ( 1053 ) is a C-13 epimer of barbatellarine D ( 1054 ), as confirmed by a NOE difference experiment and the respective NOESY spectra. 333 …”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 87%
“…Subsequently, the chemical structure of scutebarbatine F was revised by Wang et al (2010). Furthermore, the compound with the same chemical structure was also reported to be names as barbatine C and scutebata F (Nguyen et al, 2009;Zhu et al, 2010). In an attempt to obtain new biologically active neo-clerodane diterpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HMBC correlations of H-11 with C-13, H-12 and H-14 with C-16, and H-16 with C-15 supported the proposed 13-spiro-15,16-γ-lactone skeleton of 1 (Figure ). The configuration of 1 was deduced from the interpretation of the NOESY spectrum and comparison of NMR data with reported values. ,, The chemical shifts at δ H 2.61, 3.07 (H 2 -14, Δ = 0.46 ppm) and δ C 44.4 (C-14) and 76.5 (C-16) were indicative of a 13 S form, whereas the chemical shift for the 13 R form in compound 3 would be at δ H 2.51 and 2.68 (H 2 -14, Δ = 0.17 ppm) and at δ C 42.5 (C-14) and 80.0 (C-16) . The 13 S* -spiro chiral center was further determined by a NOESY correlation between H 2 -16 and H 3 -17 (Figure ).…”
mentioning
confidence: 97%
“…barbata has been used in traditional medicine as an anti-inflammatory, antihepatitis, and antitumor agent . This plant is known as a source of neo -clerodane diterpenoids, and more than 150 neo -clerodane diterpenoids have been isolated from this genus. Previous biological studies of these neo -clerodane diterpenoids have demonstrated their promising cytotoxic activity against several cancer cell lines. In the course of a research program for the isolation of anti-inflammatory constituents from medicinal plants, a MeOH extract of the aerial parts of S. barbata showed significant inhibitory effects against LPS-induced nitric oxide (NO) production (IC 50 value of 32.5 μg/mL).…”
mentioning
confidence: 99%